Healing properties of epidermal growth factor and tocotrienol-rich fraction in deep partial-thickness experimental burn wounds - Guo, Hui Fang; Abd Hamid @ Abdul Razak, Roslida; Mohd Ali, Razana; Chang, Sui Kiat; Rahman, Mohammed Habibur; Zainal, Zaida; Khaza'ai, Huzwah (MDPI, 2020)
Background: An experimental study was undertaken to determine the efficacy of the epidermal growth factor (EGF) with tocotrienol-rich fraction (TRF) cream in the wound-healing process on skin with deep partial-thickness burn in rats. Methods: A total of 180 Sprague-Dawley rats were randomly divided into six groups of six each and were: untreated control, treated with Silverdin® cream, base cream, base cream with c% EGF, base cream with 3% TRF or base cream with c% EGF and 3% TRF, respectively. Creams were applied once daily for 21 consecutive days. Six animals from each group were sacrificed using anaesthetic overdose on the third, seventh, 11th, 14th and 21st day post-burn. Skin tissues with the wound to be examined were excised for macroscopic and microscopic evaluation and biochemical analyses. Results: EGF + TRF formulation decreased the number of neutrophils, lymphocytes and myofibroblasts post-burn. However, no effects on the number of adipose cells in the healing process were recorded. In addition, lipid peroxidation and nitrite production were found to be reduced post-burn, reducing oxidative stress. Conclusions: Results of the present study indicate that the addition of EGF with TRF have ameliorating effects on deep-partial thickness burn healing parameters.